The Influence of Content Marketing, Influencer Marketing, and Paid Advertising on Purchase Decisions in Blibli E-Commerce - Tanamal, Willson; Nazmi, Hendra; Dewi, Sri Puspa (GoAcademica Research & Publishing, 2025)
This study examines the influence of Content Marketing, Influencer Marketing, and Paid Advertising on consumer purchase decisions within Blibli, one of Indonesia’s major e-commerce platforms. The research was conducted using a quantitative approach with a sample of 100 respondents collected via online questionnaires distributed to active Blibli users. Multiple linear regression analysis was used to measure the partial and simultaneous effects of the three marketing variables on purchase decisions. The findings indicate that Content Marketing has a significantly positive effect on purchase decisions, suggesting that informational content is a big difference maker to stimulate purchasing behavior. Influencer Marketing also shows a positive and significant effect, indicating that credibility, relatability, and parasocial dynamics strongly contribute to consumer trust and purchase tendencies. Paid Advertising also demonstrates a positive and significant influence, revealing that targeted exposure and platform-sponsored promotions effectively convert consumer interest into transactions. Simultaneously, all three variables together have a significant effect, showing that integrated marketing strategies produce stronger consumer responses than isolated initiatives. The study concludes that Blibli and its partnered sellers should continue to use all three advertising methods and optimize paid advertising regularly to maintain content quality and to support brand retention. Recommendations for future research include expanding sample diversity and examining additional psychological constructs such as consumer trust, brand loyalty, and perceived value.